SMART VILLAGE PROGRAM: CHALLENGES OF IMPLEMENTATION IN DIGITALIZATION ERA - Putri, Annisa; Rahayu, Desita; Dwisnu, Erlian (Universitas Djuanda, 2024)
The government targets 3000 villages to be included in the smart village program in 2024. Smart villages can support the management of existing resources and potential. Nakau village is one of villages implementing the smart village program. The village has characteristics of diverse community and different cultures, so that the implementation model must be different. Therefore, identifying factors that support the smart village program is essential. This research aims to identify the factors that influence the implementation of smart village program in Nakau village. Goggin's theory is a tool for observing the five elements, namely the series of decisions, the content of decisions and the form of decisions, constraints at the regional level, regional decisions and capacity, and feedback. This is a qualitative descriptive study; the analysis unit consists of all stakeholders involved in this program, including the village's officers, the community, digital ambassadors and cadres, the government, and other parties. Informants are drawn by purposive sampling. Data are collected by observation, documentation studies, and interviews. Data are interactively analyzed. The smart village program in Nakau village has been implemented. Several activities are already underway. However, a process is needed for the program to be perfectly implemented. The factors that influence the implementation of the smart village program in Nakau village are related to the problem of time and budget. For the program, it is a relatively new implementation, so that the stakeholders need time to implement the program and the implementation budget disbursement.